PeERF1, a SHINE-Like Transcription Factor, Is Involved in Nanoridge Development on Lip Epidermis of Phalaenopsis Flowers - Lai, Pei-Han; Huang, Li-Min; Pan, Zhao-Jun; Jane, Wann-Neng; Chung, Mei-Chu; Chen, Wen-Huei; Chen, Hong-Hwa (Frontiers in Plant Science, 2020)
Phalaenopsis orchids have a spectacular floral morphology with a highly evolved lip offering a landing platform for pollinators. Previously, we identified a member of the AP2/EREBP family highly expressed in lip by using microarray. Here, we further analyzed and confirmed its high expression in lip and characterized its function during lip development. Phylogenetic analysis showed that the AP2/EREBP protein was assigned to the Va2 subgroup of ERF transcription factors and thus named PeERF1. The occurrence of orchid lip heavy cuticle related to nanoridge coverage was concomitant with the expression of PeERF1 at the late stage of lip development. Knockdown PeERF1 expression in Phalaenopsis orchids was performed using CymMV-based virus-induced gene silencing in either ap2 conserved domain or shn specific domain. The number of nanoridges was reduced on both abaxial and adaxial surfaces of central lobe of lip in PeERF1_ap2_silenced plants but not in the PeERF1_shn_silenced plants as analyzed by Cryo-SEM. Expression of PeERF1 was reduced significantly in PeERF1_ap2_silenced plants but to a less extent in the PeERF1_shn_silenced plants. An off-target silencing effect was detected for a closely related gene, PeSHN1, and its expression was significantly reduced in both silenced plants. For cutin biosynthesis genes, expression of both PeCYP86A2 and PeDCR were significantly decreased in both silenced plants, and similar to that of PeSHN1. Yet, the expression of PeCYP77A4 was reduced significantly in PeERF1_ap2_silenced plants but to a less extent in the PeERF1_shn_silenced plants, and was similar to that of PeERF1. In contrast, expression of PeGPAT was mildly reduced in both silenced plants. In addition, the expressions of PeERF1 significantly reduced in petal-like lip of a big-foot somaclonal variant with an enlarged petal-like lip than in lip of normal plant, accompanied with the reduced expressions of PeCYP77A4 and PeGPAT in petal-like lip than in lip, but not PeDCR. Furthermore, heterologous overexpression of PeERF1 in Arabidopsis showed shiny leaves on the adaxial surface. PeERF1 and PeSHN1 together played important roles in nanoridge formation for lip epidermis development. The typical orchid lip cuticle features of nanoridge coverage are probably essential for the special pollination mechanism of Phalaenopsis flowers.